Narrative Review the Effectiveness of Hypnobirthing in Reducing Pain Scale in Mothers Giving Birth - Lisa, Ulfa Farrah; Hardisman, Hardisman; Hudzaifah, Hindun Mila; Fadila, Zurayya; putri, Joana Rahma; Purna, Rozi Sastra (Women, Midwives and Midwifery, 2025)
Background: Pain during labor can be caused by unmanaged anxiety, then causing tension in the lower uterine segment, cervix, and ischemia in the uterine muscles so the sensation and intensity of pain felt during labor is getting stronger. Hypnobirthing is one of the actions that can be done to reduce pain during labor. Purpose: This study aims to determine the effectiveness of hypnobirthing in reducing the scale of pain in mothers giving birth. Methods: This type of research is a narrative literature review using PICO. Article searches are accessed through several databases, including Pubmed, Sciencedirect, Google Scholar, and Portal Garuda. then the articles are selected based on the inclusion and exclusion criteria and then analyzed. Based on 19 journal articles that have been analyzed, the implementation of the hypnobirthing method in mothers in labor has proven effective in reducing pain during the labor process. Conclusion: The benefits of hypnobirthing that directly affect the mother are that it can make the mother feel comfortable and relaxed during the labor process, and reduce the production of catecholamine and adrenaline hormones but increase the endorphin hormone in the mother, proven to be successful in reducing the scale of pain in mothers giving birth. However, there are several factors that affect the effectiveness of hypnobirthing, such as when hypnobirthing is done, how consistently the mother does hypnobirthing and also how focused the mother is on doing deep relaxation as one of the stages of hypnobirthing itself. Further research should be conducted on the combination of the hypnobirthing method with other pain management to determine the effectiveness of this management in reducing pain during the labor process.